STRATEGI PENINGKATAN PENCAPAIAN PENDAFTARAN TANAH SISTEMATIS LENGKAP BERDASARKAN PEMBAGIAN KLUSTER BIDANG TANAH DI DESA TAMBELANG KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN (A Complete Systematic Land Registration Achievement Strategy Based On Distribution Of Land Clusters In Tambelang Village, Maesaan District, Minahasa Selatan District) - nFN Haryanto; Sherly Jocom; Leonardus R. Rengkung (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
Land is a very important factor in life, so legal certainty and legal protection for owners of the land they own are very important. Complete Systematic Land Registration is one way to accelerate land registration in order to provide legal certainty and legal protection as well as improve community welfare. In 2019, Tambelang village is one of the villages that is the location of PTSL with low achievement for cluster 1 (certificate products). The purpose of this study was to determine the causes of the low achievement of cluster 1 and strategies to increase the achievement of cluster 1 from cluster 2 and cluster 3 as well as updating cluster 4 data. This type of research is qualitative and quantitative research. Qualitative research is to determine the cause of the low achievement of K1 as a product of PTSL certificates and quantitative research to determine strategies for increasing certificate products or K1 from K2, K3 and updating data using SWOT analysis. The data in this study consisted of primary data and secondary data. Sampling using proposive sampling techniques and conducting in-depth interviews and conducting FGD (Focus Group Discussion). The results of this study can be concluded that the cause of the low achievement of K1 in the implementation of PTSL is socialization. less than optimal, lack of juridical personnel, a fee of Rp. 350,000, - the community still lacks understanding of the importance and benefits of certificates and problematic land parcels. Based on the data analysis, it can be concluded that the strategy of increasing the achievement of PTSL from cluster 2 to cluster 1, by means of the village government facilitating the resolution of problems related to land parcel boundaries and land ownership by amicable deliberation by providing a place in the General Meeting Hall, cluster 3 to cluster 1, by means of the village government provides cross subsidies related to administrative costs, carries out cooperation between the Regional Government and BPN in the context of providing administrative funds for certificate management and utilizing technological developments to reach people who are outside the location, updating cluster 4 data, by utilizing the understanding of physical officers and village governments to improve public understanding of the importance of plotting and adding staff archives to improve the quality of archiving.Keywords: Strategy, Land, Land Registration, Legal Certainty